Biomechanical Analysis of Biodegradable Cervical Plates Developed for Anterior Cervical Discectomy and Fusion - Cho, Pyung Goo (Asian Spine J, 2018)
STUDY DESIGN: In-vitro biomechanical investigation. PURPOSE: To evaluate the biomechanical effects of the degeneration of the biodegradable cervical plates developed for anterior cervical discectomy and fusion (ACDF) on fusion and adjacent levels. OVERVIEW OF LITERATURE: Biodegradable implants have been recently introduced for cervical spine surgery. However, their effectiveness and safety remains unclear. METHODS: A linear three-dimensional finite element (FE) model of the lower cervical spine, comprising the C4–C6 vertebrae was developed using computed tomography images of a 46-year-old woman. The model was validated by comparison with previous reports. Four models of ACDF were analyzed and compared: (1) a titanium plate and bone block (Tita), (2) strong biodegradable plate and bone block (PLA-4G) that represents the early state of the biodegradable plate with full strength, (3) weak biodegradable plate and bone block (PLA-1G) that represents the late state of the biodegradable plate with decreased strength, and (4) stand-alone bone block (Bloc). FE analysis was performed to investigate the relative motion and intervertebral disc stress at the surgical (C5–C6 segment) and adjacent (C4–C5 segment) levels. RESULTS: The Tita and PLA-4G models were superior to the other models in terms of higher segment stiffness, smaller relative motion, and lower bone stress at the surgical level. However, the maximal von Mises stress at the intervertebral disc at the adjacent level was significantly higher in the Tita and PLA-4G models than in the other models. The relative motion at the adjacent level was significantly lower in the PLA-1G and Bloc models than in the other models. CONCLUSIONS: The use of biodegradable plates will enhance spinal fusion in the initial stronger period and prevent adjacent segment degeneration in the later, weaker period.